Types of Flouting Maxims In A Star Is Born Movie - Mery Kristiani; Ni Made Verayanti Utami; I Wayan Juniartha (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
Abstract - Flouting maxims happens when speakers may flout a maxim or they fail to fulfil the maxims of Cooperative Principle to convey hidden meaning in their utterances. This study is concerned on finding out the types of flouting maxims that used by the characters in the movie A Star Is Born. This study was applied the theory of pragmatics from Grice (1975) to find out the types of flouting maxims and supported theory of context of situation from Halliday and Hasan (1989). The data were collected by direct observation method and analysed by descriptive qualitative method. The finding is presented in formal and informal method. Our finding shows that there are four types of flouting maxims which predominantly used by the characters in the movie A Star Is Born, they are: flouting maxim of quantity (45%), flouting maxim of quality (10%), flouting maxim of relevance (30%) and flouting maxim of manner (15%). Keywords: cooperative principle, flouting maxims, utterance, movie